Implementation of the National Online Samsat System (e-Samsat) in Palopo’s Digital Era - Ni Gusti Ayu Wiradani; Puput Flora Arifuddin; Nur Ilman (TEPIAN, 2025)
This article discusses the implementation of the National Online One-Stop Single Administration System (e-Samsat) as part of the digital transformation of public services in Palopo City. The main focus of this research is to evaluate the effectiveness of e-Samsatservices in improving the administrative efficiency of Motor Vehicle Tax (PKB) payments and encouraging taxpayer compliance. The e-Samsat service is expected to be a solution to the constraints in the conventional system, such as long queues, complex bureaucracy, and time constraints. This research uses a mixed method approach through field observations, in-depth interviews with Samsat employees and taxpayers, and a quantitative survey measuring user satisfaction with six aspects of the service: ease of use, payment methods, system efficiency, innovation, security, and infrastructure. The results showed that the majority of respondents felt helped by the existence of e-Samsat, especially in terms of ease of access and time flexibility. However, the system is not fully optimized as there are still stages that require physical presence, such as the five-year STNK validation. In addition, obstacles such as low digital literacy, lack of socialization, and technical disruptions such as unstable connections also affect the effectiveness of this system. The data shows that the level of taxpayer compliance fluctuates from year to year, with an improving trend in 2023-2024 as the number of vehicle units paying taxes online increases. This study concludes that the successful implementation of e-Samsat depends not only on the availability of technology, but also on infrastructure readiness, supporting policies, and active community involvement. Therefore, a system strengthening strategy is needed through improving digital infrastructure, public education, and inter-agency collaboration so that e-Samsat can function more effectively and sustainably in supporting the optimization of regional revenue and technology-based development.